PENGARUH MEDIA PEMBELAJARAN 3 DIMENSI TERHADAP HASIL BELAJAR SISWA PADA MATERI MENGENAL BANGUN RUANG - Nor Asyriah; Fitria Rahmawati (MEGA: Jurnal Pendidikan Matematika, 2023)
The teacher in delivering material uses only pictures on the blackboard and is still fixated on textbooks without using media. This resulted in the understanding obtained by students is still abstract. This study aims to determine the effect of 3-dimensional media on student learning outcomes in the subject of recognizing shapes in class II at MI Ibnu Athaillah.The research method used is experimental research with a quantitative approach and the type of research design used in this study is the Pretest-Posttest Group Design. The population in this study were all second grade students at MI Ibnu Athaillah. The researcher used a purposive sampling technique (purposive sampling), the samples in this study were students in class II C and class II D, class II C as the experimental class and class II D as the control class. Data collection techniques used by researchers in the form of tests and documentation.The results of the study showed that there was a significant influence between the three-dimensional learning media and student learning outcomes on the subject of recognizing shapes in class II at Ibnu Athaillah. This is evidenced by the results of the t-test, namely, tcount = 4.544 and ttable = 1.699 or tcount is greater than ttable so that H0 is rejected and Ha is accepted, meaning that 3-dimensional media has an influence on student learning outcomes in the material about geometric shapes. Keywords: 3D Media,Learning Outcomes,Build Space.